Trainee anaesthetist diagnosis of intraneural injection—a study comparing B-mode ultrasound with the fusion of B-mode and elastography in the soft embalmed Thiel cadaver model. (12th December 2016) - Munirama, S.; Zealley, K.; Schwab, A.; Columb, M.; Corner, G. A.; Eisma, R.; McLeod, G. A.
Abstract : Background. The incidence of intraneural injection during trainee anaesthetist ultrasound guided nerve block varies between 16% in experts and up to 35% in trainees. We hypothesized that elastography, an ultrasound-based technology that presents colour images of tissue strain, had the potential to improve trainee diagnosis of intraneural injection during UGRA, when integrated with B-Mode ultrasound onto a single image. Methods. We recorded 40 median nerve blocks randomly allocated to 0.25 ml, 0.5 ml, 1 ml volumes to five sites, on both arms of two soft embalmed cadavers, using a dedicated B-Mode ultrasound and elastography transducer. We wrote software to fuse elastogram and B-Mode videos, then asked 20 trainee anaesthetists whether injection was intraneural or extraneural when seeing B-Mode videos, adjacent B-Mode and elastogram videos, fusion elastography videos or repeated B-Mode ultrasound videos. Results. Fusion elastography improved the diagnosis of intraneural injection compared with B-Mode ultrasound, Diagnostic Odds Ratio (DOR) (95%CI) 21.7 (14.5 - 33.3) vs DOR 7.4 (5.2 – 10.6), P  < 0.001. Compared with extraneural injection, intraneural injection was identified on fusion elastography as a distinct, brighter translucent image, geometric ratio 0.33 (95%CI: 0.16 – 0.49) P  < 0.001. Fusion elastography was associated with greater trainee diagnostic confidence, OR (95%CI) 1.89 (1.69 – 2.11), P  < 0.001, and an improvement in reliability, Kappa 0.60 (0.55 - 0.66). Conclusions. Fusion elastography improved the accuracy, reliability and confidence of trainee anaesthetist diagnosis of intraneural injection.